Case Report: An Atypical Angelman Syndrome Case With Obesity and Fulfilled Autism Spectrum Disorder Identified by Microarray - Hnoonual, Areerat; Kor-anantakul, Phawin; Charalsawadi, Chariyawan; Worachotekamjorn, Juthamas; Limprasert, Pornprot (Frontiers in Genetics, 2021)
Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders which are etiologically heterogeneous. Chromosomal microarray is now recommended as the first-tier clinical diagnostic test for ASD. We performed chromosomal microarray in 16 Thai patients with ASD using an Illumina HumanCytoSNP-12 v2.1 array and found one case with uniparental disomy (UPD) of chromosome 15. Methylation-specific PCR showed abnormal methylation of the maternal SNRPN allele. Haplotype analysis revealed that the patient had received both chromosomes 15 from his father. These results were consistent with Angelman syndrome. However, his clinical features had no clinical significance for classic Angelman syndrome. He had first presented at the pediatric clinic with no speech, poor social interaction skills and repetitive behaviors consistent with ASD based on the DSM-IV criteria at 2 years of age and later confirmed by ADOS at 5 years of age. He was strikingly overweight but had no dysmorphic facies, seizures nor ataxia and was diagnosed as non-syndromic ASD, a diagnosis which was believed until at 10 years of age, his DNA was included for analysis in this current cohort study. Our findings suggest that ASD patients with unknown etiology should be considered for methylation-specific PCR testing for Angelman syndrome where chromosomal microarray is not available. In the study, we also review the clinical features of Angelman syndrome caused by UPD and the frequency of ASD in individuals with Angelman syndrome.